2021
DOI: 10.12707/rv20136
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades psicométricas do Questionário Geral de Saúde 28 itens em enfermeiros: proposta com 24 itens

Abstract: Background: The psychometric properties of measurement instruments should be assessed in different populations. Objective: To analyze the psychometric properties of the 28-Item General Health Questionnaire (GHQ-28) in nurses. Methodology: Methodological validation study of measurement instruments. Analysis of psychometric properties, exploratory factor analysis (EFA) by the principal component analysis method, and Receiver Operating Characteristic (ROC) curve, with a nonprobability sample of 1,264 nurses. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
1
2
Order By: Relevance
“…Mean GHQ-28 total score was, nevertheless, higher than the one reported by Zonp et al (2022), Salehi et al (2023), Pais Ribeiro et al (2015), Díaz-Ramiro et al (2020), Maciaszek et al (2020), Kolivand et al (2023), andAlmeida et al (2022), but slightly lower than the one found by Seabra et al (2021) and Babicki et al (2021); the standard-deviation was higher than the ones presented in Table 2.…”
Section: Health Professionals' Mental Health Hope and Resilient Copingcontrasting
confidence: 65%
See 2 more Smart Citations
“…Mean GHQ-28 total score was, nevertheless, higher than the one reported by Zonp et al (2022), Salehi et al (2023), Pais Ribeiro et al (2015), Díaz-Ramiro et al (2020), Maciaszek et al (2020), Kolivand et al (2023), andAlmeida et al (2022), but slightly lower than the one found by Seabra et al (2021) and Babicki et al (2021); the standard-deviation was higher than the ones presented in Table 2.…”
Section: Health Professionals' Mental Health Hope and Resilient Copingcontrasting
confidence: 65%
“…Regarding Somatic symptoms, the mean score of the present sample was the highest among the studies summarized in Table 2. Inversely, the Anxiety and insomnia mean score was lower than the ones reported by Seabra et al (2021), Maciaszek et al (2020), andBabicki et al (2021), with the samples studied by Díaz-Ramiro et al (2020) and Kolivand et al (2023) having a lower social dysfunction mean score. Finally, only the sample assessed by Kolivand et al (2023) had a mean Severe depression score higher than the present sample.…”
Section: Health Professionals' Mental Health Hope and Resilient Copingcontrasting
confidence: 55%
See 1 more Smart Citation
“…Although researchers and clinicians have a wide variety of techniques to assess adults' mental health, the GHQ-28 is frequently used worldwide. In fact, in recent years, before and during the COVID-19 pandemic, it was administered to several samples of health professionals around the globe (when available, mean and standard deviation values of these samples are presented in the Section 4) ( [20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Healthcare Professionals' Mental Healthmentioning
confidence: 99%
“…Derived from an exploratory factor analysis (EFA) of the original GHQ-60, the GHQ-28 was initially crafted in English for the London populace, subsequently undergoing translation into multiple languages worldwide (Hjelle et al, 2019). Comprising four distinct subscales, each encompassing seven items, the GHQ-28 encompasses somatic symptoms (items 1-7), anxiety and insomnia (items 8-14), social dysfunction (items 15-21), and severe depression (items [22][23][24][25][26][27][28]. Respondents rate items on a 4-point Likert-type scale ranging from 0 to 3.…”
Section: Introductionmentioning
confidence: 99%